Odpowiedzi

2009-09-12T16:27:24+02:00
(-1½)(do potęgi 7) x (-1½) : (-1½)(do potęgi 6)=(-1½)(do potęgi 2)

(-1½)(do potęgi 5) x (-1½) (do potęgi 8) : (1½) (do potęgi 11) =
=(-1½)(do potęgi 2)
Najlepsza Odpowiedź!
2009-09-12T16:39:01+02:00
(-1½)(do potęgi 7) x (-1½) : (-1½)(do potęgi 6)=(-1½)⁸: (-1½)(do potęgi 6)
(-1½)²=9/4=2¼

(-1½)(do potęgi 5) x (-1½) (do potęgi 8) : (1½) (do potęgi 11)=(-1½)¹³: (1½) (do potęgi 11)=(-1½)²=9/4=2¼
2009-09-12T17:16:50+02:00
(-1½)⁷ x (-1½) : (-1½)⁶ = (-1½)⁸:(-1½)⁶=(-1½)²=2¼
(-1½)⁵ x (-1½)⁸ : (1½)¹¹=(-1½)¹³:(-1½)¹¹=(-1½)²=2¼